Transcode in the Era of Technology and New Media - Rafee, Y.M (Faculty of Arts and Design, Universitas Sebelas Maret, Indonesai, 2018)
The participation of various parties through this exhibition, the collection of information on the perspective of art in the region and interaction within and beyond the scope will be more open. As a result of the advancement of the technological era, this global network is growing rapidly, which indirectly influences art's ability to influence other cultures, leading to the concept of a global society. Hence, this transcoding themed exhibition is hoped to be a starting point for the development and collaboration of universal artworks.